Digital Transformation and Financial Transparency in Islamic Educational Contexts - Randi Evendi Saputra; Riska Febriani; Siyfa Ulinnas; Rully Hidayatullah; Try Rama Bagus Sanjaya (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
The development of digital technology in the Society 5.0 era presented both challenges and strategic opportunities for Islamic educational institutions in realizing transparent, accountable, and efficient financial management. Professional financial governance served as a key foundation for building credibility and public trust, particularly in religious-based institutions that manage funds from the government, communities, and donors. This study aimed to analyze the urgency of implementing modern, technology-based financial management as an effort to enhance the transparency and accountability of Islamic educational institutions in Indonesia. The method employed is descriptive qualitative with a library research approach, conducted through a review of scientific literature, regulations, and the application of financial technology in the education sector. The results indicate that the integration of technologies such as cloud-based accounting systems, block chain, and digital financial applications can accelerate reporting, reduce the risk of fraud, and support real-time, data-driven decision-making. These findings confirm that digital transformation in financial management is a strategic necessity for strengthening governance, increasing stakeholder trust, and reinforcing the role of Islamic educational institutions in shaping future generations in the digital era.